The Comparative Study of the Phytochemicals of Andrographis Paniculata and Rauvolfia Vomitoria for Their Medicinal Function in the Treatment of Some Ailment - H, Audu; A, Ajibade G.; O, Abdulsalami M. (African Journal of Clinical Medicine and Pharmacy Research, 2024)
This study was carried out to compare the phytochemicals in the leave, stem and root of both Andrographis paniculata and Rauvolfia vomitoria as well as to determine and compare the quantity of alkaloid in the leave extract due to their numerous medicinal values and difference in their origin. Medicinal Plants are sources of important therapeutic aid for alleviating human ailments. Andrographis paniculata (Nees) and Rauvolfia vomitoria Afzel belong to the family of Apocynaceae.The genus are evergreen trees and shrubs. Research has shown that different parts of Andrographis paniculata indigenous to India are used for various diseases such as fever, dysentery, snake and insect bite, boils, hypertension etc while Rauvolfia vomitoria indigenous to Africa is traditionally used as an emetic, purgative and in the treatment of jaundice, gastrointestinal diseases, psychiatric disorders etc. The aqueous plant extracts were subjected to qualitative and quantitative screening using standard procedure. The result showed that paniculata contains more phytochemical than vomitoria but both plants contain the same amount of alkaloid in the leave extract which is said to be the active ingredient for the treatment of several ailments. Hence, there is the need to propagate their growth and standardize drugs from both plants.